Modern look at pathogenetic mechanisms of joint disease in patients with ixodic tick-borne borreliosis - G. G. Reshetova; O. V. Shvtsova (Бюллетень сибирской медицины, 2009)
The modern look at pathogenetic mechanisms of joint disease in patients with exodic tick-borne borreliosis is presented. The problems of etiology, pathogenesis, classifications, and morphological peculiarities of Lyme-arthritis and mechanisms of development of immune inflammation are considered.